2018
DOI: 10.1086/700278
|View full text |Cite
|
Sign up to set email alerts
|

Observations on the Life History and Geographic Range of the Giant Chemosymbiotic Shipworm Kuphus polythalamius (Bivalvia: Teredinidae)

Abstract: Kuphus polythalamius (Teredinidae) is one of the world's largest, most rarely observed, and least understood bivalves. Kuphus polythalamius is also among the few shallow-water marine species and the only teredinid species determined to harbor sulfur-oxidizing chemoautotrophic (thioautotrophic) symbionts. Until the recent discovery of living specimens in the Philippines, this species was known only from calcareous hard parts, fossils, and the preserved soft tissues of a single large specimen. As a result, the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 23 publications
(36 reference statements)
0
12
0
Order By: Relevance
“…Several shipworm species, such as Kuphus polythalamius, live in other substrates. For example, K. polythalamius is often found in sediment habitats (as well as in wood) where its gill symbionts are crucial to sulfide oxidation and carry out carbon fixation (7,22). K. polythalamius lacks significant amounts of cellulolytic symbionts such as T. turnerae and instead contains Thiosocius teredinicola, which oxidizes sulfide and generates energy for the host (23).…”
mentioning
confidence: 99%
“…Several shipworm species, such as Kuphus polythalamius, live in other substrates. For example, K. polythalamius is often found in sediment habitats (as well as in wood) where its gill symbionts are crucial to sulfide oxidation and carry out carbon fixation (7,22). K. polythalamius lacks significant amounts of cellulolytic symbionts such as T. turnerae and instead contains Thiosocius teredinicola, which oxidizes sulfide and generates energy for the host (23).…”
mentioning
confidence: 99%
“…All previously described shipworm genera are obligate wood-borers [2,3], including the giant chemoautotrophic shipworm Kuphus polythalamius , which has been shown to inhabit wood early in its life cycle and is now thought to transition to sediments after initial settlement and metamorphosis on wood [5]. However, it seems unlikely that L. abatanica makes a similar transition from wood to rock.…”
Section: Discussionmentioning
confidence: 99%
“…As the 18S and 28S rRNA gene sequences from both specimens (lot PMS-4316M) were identical, sequence data from only one specimen was concatenated and aligned as in Distel et al [9] and Shipway et al . [7] with sequences representing 11 of 17 recognized genera of Teredinidae [2,5,7,10,11] including: Bankia Gray 1842, Dicyathifer Iredale 1932, Kuphus Guettard 1770, Lyrodus Gould 1870, Nausitora Wright 1864, Neoteredo Bartsch 1920, Spathoteredo Moll 1928, Teredo Linnaeus 1758, Teredora Bartsch 1921, Teredothyra Bartsch 1921, and Tamilokus Shipway, Distel & Rosenberg, 2018, as well as 39 bivalve reference taxa. Phylogenetic analysis was performed using M r B ayes v. 3.2.6 [12] with the GTR + I + Γ nucleotide substitution model as selected using j M odel T est v. 2.1.10 [13] with Akaike Information criterion.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Like most animals that consume wood, teredinids rely on heterotrophic (cellulolytic) bacterial symbionts to supply enzymes that aid in the digestion of wood [5][6][7]. Unlike more typical members of the family Teredinidae, K. polythalamius inhabits both wood and organic-rich marine sediments [8]. It was recently shown that this atypical species harbours intracellular thioautotrophic symbionts instead of cellulolytic bacteria in its gills [9].…”
mentioning
confidence: 99%